PENGARUH PENGAWETAN GARAM KCL PADA KUALITAS KULIT IKAN BUNTAL (Arothon reticularis) - R. L. M. Satrio Ari Wibowo; Emiliana Anggriyani (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
This study aims to explain the effect of preservation with KCl on the quality of the puffer fish skin. The material used in this study was 50 pufferfish skin tail. The research was conducted in June to August 2015 in the Waste Laboratory of Polytechnic ATK and LPPT Universitas Gadjah Mada. Puffer fish skin preservation is done by soaking the skin puffer fish in each saturated KCl at a concentration 200Be and preserve skin blushes puffer fish with salt KCl for 4 weeks. Results of the reasearch were analyzed by descriptive analyses. The results showed that the longer the curing time, the levels of KCl in the skin of puffer fish is increasing, conversely levels of KCl in a saturated solution decreases. Conclusion of this research is KCl be used for preservation of puffer fish.